Investigation of selenization and various CBD CdS deposition conditions to fabricate high performing spray pyrolysis synthesized Cu(In,Ga)(S,Se) 2 solar cells - Hassan, Muhammad Aamir (2018)
Semiconducting thin-films of CIGS were deposited by spray pyrolysis of aqueous precursor solutions. The as-sprayed thin films were then selenized at different temperatures and durations to obtain the optimized selenization conditions (500 °C for 10 min). The chemical bath deposition process was used to deposit cadmium sulphide (CdS) using two different cadmium sources (cadmium acetate and cadmium sulphate) at various deposition times followed by post CdS annealing. Solar cells fabricated with CdS as the buffer layer using cadmium acetate show power conversion efficiency of 9.91% owing to its higher transmission and smaller grain size.